SEJARAH PERPINDAHAN TITIK NOL KOTA PEKANBARU DARI SENAPELAN KE JALAN JENDERAL SUDIRMAN - Wulandari, Siti; Melay, Ridwan; ', Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:Pekanbaru City development begins trading center Siak River bank in the area Senapelan, and from there the actual zero point of Pekanbaru is located. The zero point of Pekanbaru when it is marked by a small monument in the area of Indonesia Godown I, Kampung Bandar. The square-shaped stone monument with a height of approximately 70 cm and engraved Pb.0, Pad 313, Bkn 65. (Pb are Pekanbaru, Pad means Padang City and Bkn means Bangkinang City).However, in 2011 was made a monument called the monument Zapin is now recognized to be the zero point of Pekanbaru. Displacement of the zero point is being debated and will shift the identity of the city of Pekanbaru.The purpose of this study is 1) to know the history of the city of Pekanbaru 2) to determine the beginning of the laying of the zero point of Pekanbaru 3) to determine the cause of the zero point of Pekanbaru moved 4) to determine the effect displacement of the zero point of Pekanbaru. The method used in this research is the method of historical research. The technique that use is an analytical technique that is descriptive analysis approach that is used to describe a state or condition with respect to the zero point of the displacement Influence of Senapelan to Sudirman Pekanbaru, which is associated with the existing theory and the data obtained, so it seems obvious conclusion. Results from this study is the influence that occurs due to migration of zero to Sudirman monument that was originally located in the area of Senapelan. Among count automatic distance changing, people's views will be zero, and the downtown area being the same, and the main thing is the identity of the city slightly shifted because that. Simply put, the calculation of the initial distance specified by monument zero point in Senapelan now be changed. Furthermore, the society's perspective on an area of zero point and the center of town to be the same, due to similarities layout is influenced by the movement of the zero point of Pekanbaru.Key Words: Displacement, Kilometer Zero Point, Pekanbaru City